2007
DOI: 10.1111/j.1460-9568.2007.05488.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficit of NMDA receptor activation in CA1 hippocampal area of aged rats is rescued by d‐cycloserine

Abstract: Activation of the glycine modulatory site of the N-methyl-D-aspartate glutamate receptor (NMDAR) may reduce cognitive impairments associated with normal ageing. In order to test this hypothesis, we assessed the effects of the partial agonist D-cycloserine (DCS) on cellular activities involved in memory formation. This was performed in CA1 cellular networks of adult and aged Sprague-Dawley rat hippocampal slices using extracellular field excitatory postsynaptic potential recordings. Synaptic potentials specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 59 publications
10
59
0
Order By: Relevance
“…In the current study, participants who received DCS showed greater potentiation of the VEP following HFvS compared with participants who received placebo. This is consistent with prior findings that DCS augmented increases in motor cortex excitability following anodal transcranial direct-current stimulation in humans (37) and augmented LTP in rat hippocampus following high-frequency electrical stimulation (38,39). Our finding is also consistent with preclinical studies demonstrating that potentiation of the VEP following HFvS is NMDAR dependent (8).…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, participants who received DCS showed greater potentiation of the VEP following HFvS compared with participants who received placebo. This is consistent with prior findings that DCS augmented increases in motor cortex excitability following anodal transcranial direct-current stimulation in humans (37) and augmented LTP in rat hippocampus following high-frequency electrical stimulation (38,39). Our finding is also consistent with preclinical studies demonstrating that potentiation of the VEP following HFvS is NMDAR dependent (8).…”
Section: Discussionsupporting
confidence: 82%
“…Because levels of basal excitatory synaptic transmission are normal in NCAM Ϫ/Ϫ mice, it is unlikely that a GluN2B-mediated increase in the basal activity of p38 MAPK (Kochlamazashvili et al, 2010) could depress basal transmission such that LTD would be occluded. Therefore, the impaired LTD in NCAM Ϫ/Ϫ mice is most likely due to a deficit in signaling via GluN2A-containing receptors, which is restored by DCS, as also has been reported for aged rats (Billard and Rouaud, 2007). In contrast, application of DCS in NCAM ϩ/ϩ mice increased GluN signaling to levels above the threshold for LTD induction, thus impairing LTD induction.…”
Section: Discussionsupporting
confidence: 61%
“…DCS is known to rescue deficits in GluN-dependent LTP in 23-to 27-month-old wild-type rats (Billard and Rouaud, 2007) and injured mice (Yaka et al, 2007). Two-way ANOVA of LTP levels in untreated and DCS-treated NCAM ϩ/ϩ and NCAM Ϫ/Ϫ mice revealed significant effects of genotype ( p ϭ 0.006) and DCS ( p ϭ 0.003) and a significant interaction between genotype and DCS ( p ϭ 0.002).…”
Section: Glun-but Not L-vdcc-dependent Ltp Is Impaired In Ncammentioning
confidence: 99%
“…Glutamatergic activity and NMDA receptor density in the basal ganglia increase in patients with PD (23). Cycloserine is able to pass blood-brain barrier and enter the brain tissue where it acts as a partial agonist by binding to the binding site of the NMDA receptor (9). The effects of cycloserine on MPTP-induce motor disturbance may be related to increased neurotransmitter release and function in several inter-related cortical and subcortical systems.…”
Section: Discussionmentioning
confidence: 99%
“…Cycloserine, an anti-tuberculosis antibiotic, is a partial agonist of the glycine binding site of the N-methyl-D-aspartate (NMDA) receptor which improves object recognition in MPTP-lesioned monkeys (8), spatial navigation and learning deficits in aged rats (9,10) and anxiety-like behavior in rats (11,12).…”
Section: Introductionmentioning
confidence: 99%